CCAFS science influences new Rainforest Alliance standard covering 2.3 million farmers globally - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The approach of applying risk assessment and suitability mapping at a more site specific level has found its way into the development of the new RA standard as part of the merger process with UTZ. As such, more detailed climate risk assessments, adaptation planning at the community level and consideration of future climatic risks as part of the strategy development for best management practice recommendations at the farm level are likely to be included as requirements in the new standard.